2019
DOI: 10.1002/ecs2.2885
|View full text |Cite
|
Sign up to set email alerts
|

Novel plant–insect interactions in an urban environment: enemies, protectors, and pollinators of invasive knotweeds

Abstract: Relationships between invasive plants and other species in their introduced ranges may facilitate or hinder the process of invasion. Fallopia japonica (Japanese knotweed), Fallopia sachalinensis (giant knotweed), and their hybrid Fallopia 9 bohemica (Bohemian knotweed) are widespread invasive plants in North America and Europe. These species possess extrafloral nectaries (EFNs) that attract mutualist insect protectors in their native ranges. Popillia japonica Newman, 1841 (Japanese beetle) is a primary herbivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 85 publications
(130 reference statements)
2
9
0
Order By: Relevance
“…Despite the fact that the individuals sampled in this study were predominantly female, nearly all plants effectively filled seeds. Native pollinators are active and effective in R. japonica populations (Johnson et al, 2019), though the exact routes of pollen are not completely clear. The resulting seeds are highly germinable, and the seedlings can establish in natural settings (Forman and Kesseli, 2003), so it seems likely that in addition to clonal spread, sexual reproduction is occurring in North American populations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the individuals sampled in this study were predominantly female, nearly all plants effectively filled seeds. Native pollinators are active and effective in R. japonica populations (Johnson et al, 2019), though the exact routes of pollen are not completely clear. The resulting seeds are highly germinable, and the seedlings can establish in natural settings (Forman and Kesseli, 2003), so it seems likely that in addition to clonal spread, sexual reproduction is occurring in North American populations.…”
Section: Discussionmentioning
confidence: 99%
“…Washing biomass not only removes the impurities, pathogen borne agents but also discards some endogenic inorganics that affect the adsorption process. Johnson et al (2019) identified fourteen species of insects including ant, fly, wasp, bee, and beetle that were considered the visitors of exotic weed Fallopia japonica. Many of them were proved to be vectors transmitting pathogens during plant-insect interactions.…”
Section: Cleaning the Biomassmentioning
confidence: 99%
“…Many of the species brought to America—including honey bees and many plants—were indigenous to the general region surrounding Europe, the Middle East, and Asia [ 126 , 130 132 ]. When honey bees and introduced plants are from similar geographic regions, these plant species are more likely to be effectivity pollinated by honey bees than by the native bees of new landscapes [ 68 , 133 , 134 ].…”
Section: Background: Apicultures In the Capitalocenementioning
confidence: 99%